Assessing Drought Risks and Implementing Effective Mitigation Strategies to Enhance Resilience in Nunukan Regency, North Kalimantan, Indonesia - Jefri, Jefri; Purnawati, Laily; Shan, Ali; Qolbi, Yahdi; Hastira, Muh Fichriyadi (Universitas Tribhuwana Tungga Dewi, 2025)
This study aims to analyze the potential for drought disasters in Nunukan Regency, North Kalimantan, as well as mitigation efforts that can be taken to reduce their negative impacts. Based on disaster mitigation theory, this study adopts two main approaches, Disaster Risk Reduction (DRR) and Disaster Risk Management (DRM), which lead to the prevention and mitigation of drought impacts. The research method used is qualitative descriptive with secondary data analysis from various related sources. The results showed that Nunukan Regency faces a serious threat of drought, with more than 1.3 million hectares of land at risk and 48,411 hectares at high risk. Structural mitigation, such as the construction of reservoirs and retention basins, as well as non-structural mitigation, such as community education and training, have proven effective in reducing the impact of drought. Further discussion shows that mitigation efforts must involve collaboration between government agencies, the private sector, and the community to increase the capacity of the region to deal with increasingly erratic climate change. In conclusion, a comprehensive, data-driven mitigation strategy can increase the Nunukan Regency's resilience to future drought disasters.Penelitian ini bertujuan untuk menganalisis potensi bencana kekeringan di Kabupaten Nunukan, Kalimantan Utara, serta upaya mitigasi yang dapat dilakukan untuk mengurangi dampak negatifnya. Berdasarkan teori mitigasi bencana, penelitian ini mengadopsi dua pendekatan utama, yaitu Pengurangan Risiko Bencana (PRB) dan Manajemen Risiko Bencana (DRM), yang mengarah pada pencegahan dan penanggulangan dampak kekeringan. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan analisis data sekunder dari berbagai sumber terkait. Hasil penelitian menunjukkan bahwa Kabupaten Nunukan menghadapi ancaman kekeringan yang serius dengan lebih dari 1,3 juta hektar lahan terancam, dan 48.411 hektar di antaranya memiliki risiko tinggi. Mitigasi struktural, seperti pembangunan waduk dan embung, serta mitigasi non-struktural, seperti edukasi dan pelatihan masyarakat, terbukti efektif dalam mengurangi dampak kekeringan. Pembahasan lebih lanjut menunjukkan bahwa upaya mitigasi harus melibatkan kolaborasi antar instansi pemerintah, sektor swasta, dan masyarakat untuk meningkatkan kapasitas daerah dalam menghadapi perubahan iklim yang semakin tidak menentu. Kesimpulannya, strategi mitigasi yang komprehensif dan berbasis data dapat meningkatkan ketahanan Kabupaten Nunukan terhadap bencana kekeringan di masa depan.